2018
DOI: 10.1029/2018gl077042
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Signature of the Agulhas Current

Abstract: Western boundary currents play an important role in the climate system by transporting heat poleward and releasing it to the atmosphere. While their influence on extratropical storms and oceanic rainfall is becoming appreciated, their coastal influence is less known. Using satellite and climate reanalysis data sets and a regional atmospheric model, we show that the Agulhas Current is a driver of the observed band of rainfall along the southeastern African coast and above the Agulhas Current. The Agulhas curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…For instance, a weaker Gulf Stream SST front leads to a decrease in cold and dry spells over Europe (O'Reilly et al, 2016), while a sharper SST front in the Kuroshio Extension increases cyclogenesis and shifts the storm track northward, causing warming over eastern Asia and the western United States that can reduce snow cover by 4-6% (O'Reilly and Czaja, 2015; Révelard et al, 2016). Variability in the warm waters of the Agulhas influences summer rainfall over parts of South Africa (Jury et al, 1993;Nkwinkwa Njouodo et al, 2018). In EBC systems, SST minima are collocated with maxima in sea level pressure that are in turn associated with alongshore wind stress, wind stress curl, and cloud cover along the boundary (Sun et al, 2018), suggesting coupling with the full Hadley-Walker tropical atmospheric circulation, though the details of such coupling remain an open question.…”
Section: Climate and Weathermentioning
confidence: 99%
“…For instance, a weaker Gulf Stream SST front leads to a decrease in cold and dry spells over Europe (O'Reilly et al, 2016), while a sharper SST front in the Kuroshio Extension increases cyclogenesis and shifts the storm track northward, causing warming over eastern Asia and the western United States that can reduce snow cover by 4-6% (O'Reilly and Czaja, 2015; Révelard et al, 2016). Variability in the warm waters of the Agulhas influences summer rainfall over parts of South Africa (Jury et al, 1993;Nkwinkwa Njouodo et al, 2018). In EBC systems, SST minima are collocated with maxima in sea level pressure that are in turn associated with alongshore wind stress, wind stress curl, and cloud cover along the boundary (Sun et al, 2018), suggesting coupling with the full Hadley-Walker tropical atmospheric circulation, though the details of such coupling remain an open question.…”
Section: Climate and Weathermentioning
confidence: 99%
“…Mechanistically, this oceanic imprint has traditionally been associated with a time-mean atmospheric response associated with either a boundary layer pressure adjustment mechanism (Lindzen and Nigam 1987;Minobe et al 2008;Nkwinkwa Njouodo et al 2018) in which fluxdriven spatial pressure gradients drive secondary circulations (Wai and Stage 1989) or the momentum mixing anomalies induced down through the boundary layer by differential SST values (Hayes et al 1989;Wallace et al 1989). However, recent studies have shown that this band of time-mean wind convergence is dominated by synoptic storms (Parfitt 2014;Parfitt and Czaja 2016;O'Neill et al 2017) and is in fact set by atmospheric fronts embedded within them (Parfitt and Seo 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a positive correlation between sea surface temperature (SST) and near‐surface wind speed over western boundary currents (WBCs) suggest an ocean‐to‐atmosphere forcing through turbulent heat fluxes (Nonaka & Xie, ), whose variability on monthly and longer timescales is largely driven by internal ocean processes (Bishop et al, ). Studies considering the atmospheric impact of WBCs typically fall into one of two broad categories—the oceanic impact on the mean state (e.g., Shimada & Minobe, ) and on synoptic storms (e.g., Hirata et al, , ), with community efforts still very much ongoing (e.g., Nkwinkwa Njouodo et al, ; Small et al, ). One major outstanding issue, however, is a lack of mechanistic understanding concerning how these two distinct research avenues coalesce.…”
Section: Introductionmentioning
confidence: 99%